Influence of Social Media on Corporate Communication Social Responsibility Under Entrepreneurial Psychology - Cai, Mufei (Frontiers in Psychology, 2022)
The research intends to improve the optimization of social media’s nature of corporate social responsibility (CSR) and standardize the influence mechanism of social media. First, the research analyzes the concepts of social media, CSR, and corporate reputation from the perspective of entrepreneurial psychology and expounds on the influencing factors of CSR scores from a macro perspective. Second, the mechanism of social media’s role in CSR is briefly discussed. On this basis, it is found that the most intuitive manifestation of social media platforms affecting the communication of CSR is the impact on the score of CSR. Three hypotheses are proposed, namely, (1) social media platforms, such as “WeChat,” have a greater impact on the communication of CSR; (2) social media is positively correlated with the increase in CSR scores; and (3) user reading and liking are positively correlated with the increase in CSR scores. Finally, 78 listed companies related to the mobile communication industry are selected as samples for the questionnaire survey and statistical analysis, and the hypothesis is demonstrated. The results demonstrate that the hypothesis that the social media platform “WeChat” has an impact on the communication of CSR is valid, and the hypothesis that the open state of “social media” is positively correlated with the increase in CSR scores is not valid. It is assumed that the number of user readings and likes is positively correlated with the increase in CSR score, which is valid under a limited sample. It is concluded that the WeChat platform has the best effect on the communication of CSR and can provide the impetus for the improvement of corporate reputation. The opening of “social media” is not directly related to the improvement of CSR scores. The correct operation of “social media” will have an impact on the communication of CSR. The correlation between the number of users reading and liking on “social media” and the increase in CSR score is not significant, as only the number of “likes” on social media related to shareholders is significantly associated with an increase in CSR score. The linear regression coefficient between the number of likes and the increase in CSR score is less than 0.05. There is a positive correlation between user reads, likes, and increases in CSR scores. This research helps enterprises to effectively fulfill their social responsibilities and improve the efficiency of CSR. This makes up for the lack of social media’s influence mechanism on the nature of CSR. It innovatively explores the impact of social media on CSR from the perspective of entrepreneurial psychology and provides some ideas for entrepreneurs and enterprises to create CSR and CSR value.